Kasus Pendayagunaan Sumber Daya Pendidikan - Ermi Aprilia; Afindi Afindi; Henda Saputra (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Education is an important sector in the development of a country, and effective utilization of educational resources plays a major role in achieving these goals. However, in Indonesia, the utilization of educational resources still faces various challenges, especially related to the unequal distribution of resources between urban and remote areas. This study aims to analyze the utilization of educational resources in Indonesia, both in terms of the quality of educators, educational facilities, and available technology. The research method used is a qualitative approach with descriptive analysis to describe the current conditions and existing challenges. The results of the study show that despite government efforts, there is still a large gap in access to education between developed and disadvantaged areas. Assistance programs such as the School Operational Assistance Fund (BOS) and the Smart Indonesia Program (PIP) have not fully reached areas in need. The quality of educators is also a major obstacle, especially in the 3T (frontier, outermost, and disadvantaged) areas, where many teachers have not received adequate training. In addition, the problem of uneven distribution of educational infrastructure is a major obstacle in creating a conducive learning environment. This study suggests the need for equal distribution of education budgets, improvement of teacher quality through continuous training, and more transparent and efficient management of existing education resources. The implementation of educational technology is also expected to improve the quality of learning in areas with physical limitations. In the long term, more inclusive and locally data-based policies will strengthen Indonesia's education system. This study is expected Keywords: Educational Resources, Utilization, Quality of Educators Education is an important sector in the development of a country, and effective utilization of educational resources plays a major role in achieving these goals. However, in Indonesia, the utilization of educational resources still faces various challenges, especially related to the unequal distribution of resources between urban and remote areas. This study aims to analyze the utilization of educational resources in Indonesia, both in terms of the quality of educators, educational facilities, and available technology. The research method used is a qualitative approach with descriptive analysis to describe the current conditions and existing challenges. The results of the study show that despite government efforts, there is still a large gap in access to education between developed and disadvantaged areas. Assistance programs such as the School Operational Assistance Fund (BOS) and the Smart Indonesia Program (PIP) have not fully reached areas in need. The quality of educators is also a major obstacle, especially in the 3T (frontier, outermost, and disadvantaged) areas, where many teachers have not received adequate training. In addition, the problem of uneven distribution of educational infrastructure is a major obstacle in creating a conducive learning environment. This study suggests the need for equal distribution of education budgets, improvement of teacher quality through continuous training, and more transparent and efficient management of existing education resources. The implementation of educational technology is also expected to improve the quality of learning in areas with physical limitations. In the long term, more inclusive and locally data-based policies will strengthen Indonesia's education system. This study is expected